Strategy of Entrepreneurship Education Based on Digital Technology For Students In The World Working In Indonesia - Rohaetin, Sri (Universitas Islam Malang, 2020)
Unemployment and the low multidisciplinary labor market in Indonesia are multidimensional problems that are actually able to be solved. The solution the Indonesian government hopes is that unemployment can fall by increasing the quality of education and entrepreneurship. The purpose of this study is to provide a model of developing strategies that can be done to develop the potential of entrepreneurship education through the implications of digital technology so that the younger generation has the ability to start up and entrepreneurial spirit in the future. By using qualitative analysis sourced from the results of a literature study, researchers found that entrepreneurship education strategies based on local wisdom and assistance in adopting digital technology will be able to reduce unemployment and increase entrepreneurial creativity of the nation's children to compete and face the world of work. But in its development, a good collaboration is needed between support from government policies, teaching staff, and high interest and motivation from students to make it happen.